MODERASI BERAGAMA MAHASISWA PAI: ANALISIS PENGARUH TIKTOK TERHADAP TAWASSUTH, TASAMUH DAN ISLAH - Umi Mufida Hidayati; Ahmad Roihan Tamim; Ajeng Galuh; Rio Kurniawan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2025)
TikTok, a video-sharing app launched in September 2016 by Byte Dance, has become very popular in Indonesia, especially among university students. In May 2024, Indonesia became the country with the highest number of student TikTok users in the world. This study explores the role of religious moderation as a potential solution to address the issue of cyberbullying on TikTok, focusing on the values of Tawassuth (moderation), Tasamuh (tolerance), and Ishlah (rectification). This research uses descriptive quantitative methods through a survey of 83 students of the Islamic Education Study Programme of UIN Raden Mas Said Surakarta, consisting of 65 TikTok users and 18 non-users. The results showed that the majority of students agreed that they try not to discriminate against groups in the society. to not discriminate against groups in communication, respect differences, and try to improve the situation through the use of TikTok. In addition, most students also agreed that TikTok can be used as a means to establish friendship and promote religious moderation values. These findings indicate that religious moderation values can play an important role in reducing cyberbullying and promoting more positive communication on social media.